حالة الأغذية والزراعة 2018 - Organisation des Nations Unies pour l'alimentation et l'agriculture (United Nations, 2018)
Migration is an expanding global reality, one that allows millions of people to seek new opportunities. But it also involves challenges for migrants and for societies, both in areas of origin and of destination. This report analyses migratory flows – internal and international – and how they are linked to processes of economic development, demographic change, and natural-resource pressure. The focus is on rural migration, the many forms it takes and the important role it plays in both developing and developed countries. The report investigates the drivers and impacts of rural migration and highlights how related policy priorities depend on country contexts that are in continuous evolution.